PENGARUH PROSES REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PADA PT. ASTRA CREDIT COMPANIES (ACC) CABANG SAMARINDA - Reni Oviana (OBOR: Oikonomia Borneo, 2019)
The purpose of this study was to determine the effect of the recruitment and selection process on the performance of employees of PT. Astra Credit Companies Samarinda Branch AR Management Division and Knowing which variables are dominant and affect the performance of employees of PT. Astra Credit Companies Samarinda Branch AR Management Division. This research method is descriptive and associative with a quantitative approach using Multiple Linear Regression analysis tools, Coefficient of Determination Analysis and Hypothesis Testing (F Test and T Test), with the help of SPSS version 22 program to determine the effect of each variable. The results of statistical tests, the results of the F-test calculations that Fcount 10,673 > Ftable 3.42 with a sig value of 0.001 <0.05, it can be said that recruitment and selection have a positive and significant effect on employee performance. And based on the T-test, the recruitment variable obtained a tcount of 2.821 > 2.068, with a sig of 0.010 <0.05, it can be said that recruitment has a positive and significant effect on employee performance. As for the selection variable, the ttable value is 2.068, the tcount value is 1.320 < ttable 2.068, with this the sig value is 0.200> 0.05, it can be said that the selection has no positive and significant effect on employee performance.